Gold Investment and Financial Crisis: Some Theoretical Consideration - Mohd Fahmi Ghazali; Hooi Hooi Lean; Zakaria Bahari; Jasman Tuyon (Penerbit Universiti Malaysia Sabah, 2018)
Due to its unique nature, gold has always been regarded as a safe asset. A drastic shift in recent years towards investment demand from jewellery demand reflects the concept that gold can be considered a safe haven asset in times of economic turmoil since investors construct their portfolios to include more gold as an alternative to riskier assets. This paper demonstrates the relevant theoretical dimensions of the gold investment during financial crises. Specifically, we exhibit how investor behaviour has the potential to support the safe haven property of gold. Evidence from this study shows that behavioural finance theories provide valuable contributions, and can aid in improving the understanding and the ability to make better decisions.